2021
DOI: 10.1039/d1ra04316a
|View full text |Cite
|
Sign up to set email alerts
|

Calcium carbonate modified urea–formaldehyde resin adhesive for strength enhanced medium density fiberboard production

Abstract: Reactions between CaCO3 and CH2O2 during polycondensation of UF resin produce Ca2+. Ionic bond complexation binds Ca2+ with UF resin. The UF resin crystalline percentage decreases from 26.86% to 22.71%. IB strength of resin bonded fiberboard increases from 0.75 to 0.94 MPa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The poor performance of the UF resin likely stems from its chemical incompatibility with the keratin in feathers. UF primarily bonds with the hydroxyl groups found in wood cellulose, unlike the protein structures in feathers, which lack abundant hydroxyl groups and do not offer similar reactive sites for UF [31,49]. Even though there was a decrease in the IB values for the panels with feathers, they still met European standards (EN 312) requirements, except for panel 2.…”
Section: Resultsmentioning
confidence: 98%
“…The poor performance of the UF resin likely stems from its chemical incompatibility with the keratin in feathers. UF primarily bonds with the hydroxyl groups found in wood cellulose, unlike the protein structures in feathers, which lack abundant hydroxyl groups and do not offer similar reactive sites for UF [31,49]. Even though there was a decrease in the IB values for the panels with feathers, they still met European standards (EN 312) requirements, except for panel 2.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, the provision of mixed ammonium-nitrate nutrition to plants requires an adequate K supply to achieve increases in yield and protein content. Proper management of the pattern and chemical form of nutrient release from SRFs or CRFs can facilitate the beneficial physiological effects offered by these treatments [108]. However, the effects mentioned above require intensified attention, particularly on the field level, to assess their actual contribution, besides simply reducing nutrient losses [92].…”
Section: Impact Of Modified Urea Fertilizers On Crop Yield and Nuementioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/su16010188/s1. References [27,37,38,40,42,52,57,[108][109][110][111][112][113][114][115][116][117][118][119][120] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Bono et al (2006) applied 1% NH4Cl for hardening melamine ureaformaldehyde (MUF) resin and evaluated curing behavior. Lu et al (2021) produced UF resin bonded MDF using NH4Cl (1% to solid resin content) as a hardener. Atar et al (2014) reported that particles with NH4Cl present lower pH value than Al2(SO4)3 and hardener decreased pH values of wood particles with UF resin due to acid catalyzing behavior for the curing reaction of resin.…”
Section: Introductionmentioning
confidence: 99%